2019
DOI: 10.1515/ijnes-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Leadership Skills through Peer Mentoring and Teaching: the Lived Experience of BSN Students

Abstract: Although leadership theory is introduced in baccalaureate nursing curriculum, opportunities to practice and develop leadership skills are limited for undergraduate nursing students. This study explores the experience of advanced nursing students who provided mentoring and tutoring to beginning nursing students. The experiences they describe are interpreted in light of literature on leadership education in undergraduate nursing schools, as well as that of peer mentoring and peer teaching. These advanced student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…Peer mentors described experiences of mutual learning within interactions with mentees, consistent with prior studies (Bright, 2019;Christiansen and Bell, 2010;Giordana and Wedin, 2010;Smith et al, 2015). While coaching mentees, SPMs themselves were learning how to notice and respond to complex situationsa capability that is transferable to being a health care professional.…”
Section: Embodied Social Understandingsupporting
confidence: 71%
See 2 more Smart Citations
“…Peer mentors described experiences of mutual learning within interactions with mentees, consistent with prior studies (Bright, 2019;Christiansen and Bell, 2010;Giordana and Wedin, 2010;Smith et al, 2015). While coaching mentees, SPMs themselves were learning how to notice and respond to complex situationsa capability that is transferable to being a health care professional.…”
Section: Embodied Social Understandingsupporting
confidence: 71%
“…Findings from student peer mentorship research suggest that interactions between peer mentors and mentees provide mutual gain (Bright, 2019; Christiansen and Bell, 2010; Giordana and Wedin, 2010; Loke and Chow, 2007; Smith et al. , 2015), are supportive (Andersen and Watkins, 2018; Glass and Walter, 2000; Jacobs, 2017; Kramer et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that a discussion‐based (J. Kim et al, 2011 ) or situated learning model (Ailey et al, 2015 ) could be helpful in this respect. Others have suggested that peer‐mentoring programmes can help nursing students experience leadership and develop their leadership skills (Bright, 2019 ). In general, both the literature and our participants suggest that traditional, lecture‐based education does not breed leadership or help students internalize what they have learned and make considerable behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Ao vivenciar a educação em pares, seja na construção de materiais ou na tutoria propriamente dita, o discente-monitor tem a oportunidade de obter competências e conhecimento adquirido com a prática, de forma efetiva e produtiva 13 .…”
Section: Discussionunclassified